2012
DOI: 10.1111/j.1753-6405.2012.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Falling through the cracks: the gap between evidence and policy in responding to depression in gay, lesbian and other homosexually active people in Australia

Abstract: Objective: To examine the evidence for a national policy response to depression among gay, lesbian and other homosexually active people in Australia. Methods: A literature review using database searches on depression among non‐heterosexual people then a web‐based search of national policy investigating how mental health needs in this population are addressed in Australia. Results: The literature review found that non‐heterosexual people experience depression at higher rates, but the literature on interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…2 In Australia and overseas, mental health conditions, particularly depression and anxiety, have consistently been reported to be higher in LGBTI populations than in the general population, including heterosexual and cisgender people. [3][4][5] These differences are also apparent in the older population. Psychological distress has been identified as 1.42-fold greater for older gay and bisexual men (compared with older heterosexual men) and 1.35fold higher for older lesbians and bisexual women (compared with older heterosexual women).…”
Section: Introductionmentioning
confidence: 92%
“…2 In Australia and overseas, mental health conditions, particularly depression and anxiety, have consistently been reported to be higher in LGBTI populations than in the general population, including heterosexual and cisgender people. [3][4][5] These differences are also apparent in the older population. Psychological distress has been identified as 1.42-fold greater for older gay and bisexual men (compared with older heterosexual men) and 1.35fold higher for older lesbians and bisexual women (compared with older heterosexual women).…”
Section: Introductionmentioning
confidence: 92%
“…Urgently needed as the next step, however, is a concerted effort to develop innovative educational, community awareness, advocacy and health promotion approaches coupled with research on outcomes and experiences. In particular, using standardized measures for depression as an outcome from such interventions is required given the links between mental health and sexual identity in people with a lifelong disability (Carman et al, 2012). As a group of Australian researchers and practitioners, we are alarmed at the total absence of any published research from Australia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of mainstream literature identified that people who identify as LGBTIQ experience greater rates of depression when compared with heterosexual people (Carman et al, 2012). Three of the noted protective factors for depression in people who identify as LGBTIQ were (a) being in a relationship; (b) social support from peers, friends and family; and (c) a sense of belonging to a community.…”
Section: Mainstream Literature and Mental Healthmentioning
confidence: 99%
“…In prison and community settings in Australia, more attention is needed from policy makers, practitioners, and researchers to inform context-specific interventions that take into account the differences between heterosexual and GLBT populations, importantly in terms of injection drug use and risky sexual practices. Promisingly, other national strategies and policies in Australia have recognized and responded to the vulnerability of this group (as well as young people) in relation to mental health (e.g., Australia’s National Suicide Prevention Strategy ) and the need for increased access to education and information for service providers (Carman, Corboz, & Dowsett, 2012). These recommendations are critical to service providers working with prisoners.…”
Section: Discussionmentioning
confidence: 99%